Transformations of European Welfare States and Social Rights Regulation, Professionals, and Citizens - Nielsen, Stine Piilgaard Porner; Hammerslev, Ole (Palgrave Socio-Legal Studies, 2024)
This open access edited book investigates European social rights in practice from socio-legal perspectives. It brings together fourteen socio-legal scholars, representing Nordic and Western European countries, who analyse different aspects pertaining to European social rights, namely the regulation of social rights, encounters between welfare professionals and citizens, and citizens' mobilisation of social rights. These three different aspects form the structure for the sections in the anthology, each analysing transformations related to regulation, encounters and rights mobilisation. The book contributes to the existing literature as it focuses on interdependent transformations on macro, meso and micro levels which are key for understanding processes and contexts related to European social rights in practice. It speaks particularly to academics in sociology of law and/or regulation. Stine Piilgaard Porner Nielsen is an Associate Professor of Sociology of Law at Aalborg University, Denmark. Ole Hammerslev is Professor of Sociology of Law at Lund University, Sweden.